Overview of EBV-Associated T/NK-Cell Lymphoproliferative Diseases - Kimura, Hiroshi; Fujiwara, Shigeyoshi (Frontiers in Pediatrics, 2019)
Epstein-Barr virus-associated T/natural killer-cell lymphoproliferative diseases (EBV-T/NK-LPDs) are a group of rare diseases resulting from ectopic infection of T or natural killer (NK) lymphocytes with Epstein-Barr virus (EBV). EBV-T/NK-LPDs include chronic active EBV infection, EBV-associated hemophagocytic lymphohistiocytosis, hydroa vacciniforme-like lymphoproliferative disease, and severe mosquito bite allergy. Extra-nodal NK/T-cell lymphoma-nasal type and aggressive NK-cell leukemia can also be included in this broad spectrum. Currently, the etiology of EBV-T/NK-LPDs is unknown and no curative therapy has been established, except for hematopoietic stem cell transplantation. While most cases of EBV-T/NK-LPDs have been documented in specific areas of the world, they have also been documented more broadly across East Asia and Latin America. Consequently, active research and discussion of EBV-T/NK-LPDs are both necessary and important within the extensive international community of scientists and clinicians, to elucidate their etiology and develop a standard therapy.